The Role of Iraqi Satellite Channels in Shaping Public Attitudes toward the 2023-2024 Gaza War (Journal of Misan Researches, 2025)
The researcher defined the research problem with the main question: "What is the role of Iraqi satellite channels in shaping public attitudes toward the 2023-2024 Gaza War?"The research community was defined as students from the universities of Maysan Governorate (Maysan - Imam Ja'far al-Sadiq (peace be upon him) - Al-Manara - and the two colleges of Imam al-Kadhim (peace be upon him) University and Al-Amara University). The purposive research sample was defined as (250) university students, equally divided between males and females, and equally divided between scientific and humanities disciplines. This research is descriptive in nature, employing a field survey approach. The research tools were defined as two questionnaires for demographic information and exposure, and a three-dimensional scale form for measuring attitude formation. Three hypotheses were also identified, derived from media dependency theory and its main hypotheses. The time frame was set as October 2024 to measure the period from October 2023 to October 2024.The researcher reached several results, most notably:. The "mostly" category emerged as the first category in the axis of exposure to watching the events of the Gaza war on Iraqi satellite news channels.. The "watching for an hour" category emerged as the first category in the axis of exposure to watching the events of the Gaza war on Iraqi satellite news channels.. The first research hypothesis is confirmed (satellite channels contribute to shaping audience attitudes and prioritizing their views by providing them with new information and details).. The second research hypothesis is confirmed (media works to attract audiences by presenting their issues in emotional, interactive ways to influence them in one way or another).The third research hypothesis is confirmed (satellite channels' focus on specific issues leads to audience engagement with them, which then leads to behavioral positions on the ground).